The Esthetic Use of Botulinum Toxins in Cancer Patients: Providing a Foundation for Future Indications - Marco Papagni; Monica Renga; Selene Mogavero; Paolo Veronesi; Maurizio Cavallini (Toxins)
Advances in oncological treatments have improved the survival rates of cancer patients but have often resulted in significant physical changes that negatively impact their self-esteem and psychological well-being. Cancer patients frequently ask esthetic practitioners to perform procedures to address such changes. However, practitioners often hesitate to satisfy such requests due to lacking guidelines or recommendations. The use of botulinum toxins (BoNTs) for esthetic purposes has shown significant promise in improving the quality of life for cancer patients. This review explores the broad application of BoNTs in many medical branches, focusing on oncology. A substantial amount of literature shows that BoNTs are safe and effective as a type of adjunctive therapy compared to classical cancer treatments. We provide our expert opinion that the use of BoNTs for esthetic purposes is safe for cancer patients and even recommended for those whose mood is influenced by the worsening of their physical appearance. Careful patient selection and interdisciplinary collaboration are essential to the safe integration of BoNTs into cancer care.